2019
DOI: 10.1111/gcb.14535
|View full text |Cite
|
Sign up to set email alerts
|

Organic amendment additions to rangelands: A meta‐analysis of multiple ecosystem outcomes

Abstract: Interest in land application of organic amendments—such as biosolids, composts, and manures—is growing due to their potential to increase soil carbon and help mitigate climate change, as well as to support soil health and regenerative agriculture. While organic amendments are predominantly applied to croplands, their application is increasingly proposed on relatively arid rangelands that do not typically receive fertilizers or other inputs, creating unique concerns for outcomes such as native plant diversity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 126 publications
(183 reference statements)
1
56
0
Order By: Relevance
“…Organic biosolids from cities are a large pool of organic material that are often a pollution and waste disposal problem 47 , that could provide substrate to build soil health and sequester carbon in soils. Exogenous organic matter additions can stimulate rangeland productivity and sequester endogenous organic matter beyond the actual tonnage of compost/biosolids applied 48 , but may pose a risk to native plant biodiversity 49 and more research is needed (and is underway) to understand how universal these findings are. Early research from row-crop systems suggests endogenous vs. exogenous organic matter have similar effects 50 .…”
Section: Soil Science Knowledge Gapsmentioning
confidence: 99%
“…Organic biosolids from cities are a large pool of organic material that are often a pollution and waste disposal problem 47 , that could provide substrate to build soil health and sequester carbon in soils. Exogenous organic matter additions can stimulate rangeland productivity and sequester endogenous organic matter beyond the actual tonnage of compost/biosolids applied 48 , but may pose a risk to native plant biodiversity 49 and more research is needed (and is underway) to understand how universal these findings are. Early research from row-crop systems suggests endogenous vs. exogenous organic matter have similar effects 50 .…”
Section: Soil Science Knowledge Gapsmentioning
confidence: 99%
“…These amendments have been shown to improve on-ranch soil C sequestration and forage quantity and quality at two sites in Northern California (Ryals et al 2014;Ryals et al 2016). In addition, a recent global meta-analysis by Gravuer et al (2019) showed that rangeland forage production and soil C increase in the first few years following application of organic amendments. However, Gravuer et al (2019) caution that these benefits may come with trade-offs depending on the type of organic material used and the rates of application.…”
Section: Compost Amendments: Applications Increase Foragementioning
confidence: 99%
“…In addition, a recent global meta-analysis by Gravuer et al (2019) showed that rangeland forage production and soil C increase in the first few years following application of organic amendments. However, Gravuer et al (2019) caution that these benefits may come with trade-offs depending on the type of organic material used and the rates of application.…”
Section: Compost Amendments: Applications Increase Foragementioning
confidence: 99%
See 2 more Smart Citations